The correlation between heart rate variability and improvement in soccer player's physical performance. http://dx.doi.org/10.5007/1980-0037.2012v14n6p713 - Ricardo Santos Oliveira; Rafael Evangelista Pedro; Vinicius Flávio Milanez; Henrique Bortolotti; Marcelo Vitor-Costa; Fábio Yuzo Nakamura (Universidade Federal de Santa Catarina, 2012)
The aim of this study was to analyze whether the heart rate variability (HRV), assessed at the beginning of a soccer preseason, reveals a correlation with the improvement of physical performance over this training period. Ten soccer players took part in the study. Their performance was evaluated by the following tests: the Yo-Yo intermittent recovery test, Level 1(Yo-Yo IR1); the 30-m sprint time, and the vertical jump; all were conducted before and after six weeks of pre-season. The HRV measurements were performed at rest in the supine position for ten minutes. The Spearman Rank Correlation test was used to investigate any possible relationship between HRV and improvements in performance, while the Student's t-test verified the changes in both performance and HRV. The Magnitude-Based Inferences approach (qualitative analysis) was applied to verify the possibilities of the observed values being positive, negative or inconclusive. There were significant improvements in Yo-Yo IR1 performance (P< 0.001) and in the 30-m sprint time (P< 0.001). The qualitative analysis revealed that the differences in Yo-Yo IR1 performance were very likely positive, were almost certainly positive for the sprint, but were inconclusive for the vertical jump. There was a strong correlation between one parasympathetic index and the change in performance [r = 0.85 P = 0.003 (IC95% = 0.49 - 0.97)]. In conclusion, this study revealed a strong correlation between parasympathetic indices of HRV (analyzed before the training) with the performance improvement in Yo-Yo IR1 in football athletes during pre-season.